The Dilemma of Achieving "Same Case, Same Sentence" in Cases of "Knowing and Buying Counterfeits" in the Field of Food and Drugs and Its Legal Progress - Zhao, Yuhuan (Transactions on Social Science, Education and Humanities Research, 2024)
The frequent disparity in judicial rulings for identical cases of "Knowingly Purchasing Counterfeit Goods" within the food and drug sector has significantly undermined the authority of the law and compromised judicial fairness. An empirical study of 100 randomly selected judicial decisions from Shandong Province reveals that the current level of uniformity in judgments for equivalent cases is less than ideal. To delve deeper into the factors influencing these inconsistencies, this paper conducts an analysis of the suspicion of counterfeit awareness, the burden of proof, and the nature of the appellate case, utilizing the chi-square test for independence. Challenges such as establishing consumer identity, defining fraudulent behavior, and evaluating the standards of food safety are pivotal issues that impede the equitable treatment of knowingly purchasing counterfeit goods within the food and drug sector. In this distinct domain, the act of knowingly purchasing counterfeit goods, despite potential associations with professional racketeering, often yields a more constructive outcome. If it is determined that the parties involved are not engaged in commercial operations, their status as consumers should be acknowledged. When assessing food safety standards, emphasis should be placed on substantive criteria rather than mere formalities. Moreover, the presence of substantial harm should not be a mandatory threshold for the application of punitive damages. Additionally, if an operator fails to fulfill their evidentiary responsibilities or demonstrates "knowledge" of the counterfeit goods, the consumer’s claim for compensation should be upheld.